UJI EFEKTIVITAS SEDIAAN KRIM EKSTRAK ETANOL BIJI PINANG (Areca cathecu L) SEBAGAI OBAT LUKA SAYAT PADA KELINCI (Oryctolagus cuniculus) - dzulasfi; Muhammad Ilham (Jurnal Kesehatan Yamasi Makassar, 2024)
This study aims to determine the effectiveness of areca nut ethanol extract cream on healing incision wounds in rabbits. This study is an experimental study in the Laboratory using 1%, 2%, and 3% areca nut extract cream as test samples and betadine cream as a positive control and cream base as a negative control tested on rabbits. The results of this study obtained a wound healing effect on betel nut extract cream 1% by (4,25%) per day, betel nut extract cream 2% by (6,00%) per day, and betel nut extract cream 3% by (6.75%) per day.